Bruxism: A Literature Review - Reddy, S Varalakshmi (J Int Oral Health, 2014)
Parafunctional activities associated with the stomatognathic system include lip and cheek chewing, nail biting, and teeth clenching. Bruxism can be classified as awake or sleep bruxism. Patients with sleep bruxism are more likely to experience jaw pain and limitation of movement, than people who do not experience sleep bruxism. Faulty occlusion is one of the most common causes of bruxism that further leads to temporomandibular joint pain. Bruxism has been described in various ways by different authors. This article gives a review of the literature on bruxism since its first description.